MATERIALISM AND ITS EFFECT ON UNIVERSITY STUDENTS’ PERFORMANCE: THE CASE OF SOKOINE UNIVERSITY OF AGRICULTURE - Benedicto Kazuzuru (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Materialism is often defined as a tendency by an individual to admire and prefer material possessions. While it is true that almost all human beings prefer material possessions, the degree of preference and admiration of material possessions differs from one person to another. This study aimed to assess the level of materialism among university students at Sokoine University of Agriculture in Morogoro region of Tanzania. The study also intended to assess the effect of materialism on university students’ performance. In Tanzania, this field of study has rarely been investigated. The study was carried out at Sokoine University of Agriculture in 2016 in Mazimbu campus located in Morogoro urban area. Primary data were collected through structured questionnaire on students from 10 degrees programmes. Secondary data on university students’ performance were taken from SUA examination records. Data analysis was done using Likert scale, chi-square test and multiple linear regression using STATA software. Findings indicate that the university students are generally materialist with female students and young students being on the higher side of materialism than their counterparts. As regards the influence of materialism on performance, it was found that materialistic students perform poorer than students who are less materialistic, consistent with the available literature. The study recommends to the government through its universities to discourage the materialistic culture among students much as apart from leading to poor performance, it may also lead to other bad behaviors such as prostitution. This can be done through encouraging philosophical and religious studies among the university students.